Defeat, decline and disconnect: A critical analysis of attempted reform in British tennis during the inter-war period. Issue 1 (2nd January 2017) - Lake, Robert J.; Eaves, Simon J.
ABSTRACT: Of all periods in the history of British tennis, arguably the inter-war years were the most significant and tumultuous. Officials recommenced activities with an ultimate goal of restoring British prowess at an international level. This paper aims to assess the long-term effectiveness of the LTA's efforts in these regards. It was far from straightforward. After several years of lacklustre performances, a group of reformers staged a mutiny that culminated at the turbulent 1922 AGM, where they unseated several incumbent councillors. Yet they failed to shift significantly the balance of power away from the ageing establishment figures they had targeted. Nevertheless, a period of self-reflection followed, and the partially reformed LTA responded by refocusing its efforts on two key areas: the development of coaching-professionals and of tennis in the public schools. However, it was evident that deep-rooted antipathy towards the promotion of a more modern, American-inspired, performance-oriented, 'professional' mentality among players, and fears over the concomitant erosion of amateurism, underpinned the LTA's reluctance to increase access and develop talent among those outside of the upper-middle class. Fred Perry's exploits offered a temporary respite from some of the criticism, but ultimately merely proved to mask the LTA's staunch conservatism during this period.